Dimethyl ether-to-olefins over aluminum rich ZSM-5: The role of Ca and La as modifiers. (1st January 2018) - Bakare, Idris A.; Muraza, Oki; Sanhoob, Mohammed A.; Miyake, Koji; Hirota, Yuichiro; Yamani, Zain H.; Nishiyama, Norikazu
Graphical abstract: Catalytic activity and selectivity of parent and metal modified zeolites in the DTO process. Highlights: Presence of basic sites on zeolite enhanced light olefin selectivity. Metal oxide modifiers mitigated strong surface acidity. The presence of CaO species induced weak and medium acidity. Olefin selectivity was highly dependent on acid site distribution and temperature. Abstract: Dimethyl ether (DME) has a strategic role both as an alternative fuel and a feedstock for petrochemicals. Aluminum rich H-ZSM-5 modified with Ca and La species were investigated in the conversion of Dimethyl ether (DME) to olefins. The crystallinity and morphology of Ca-ZSM-5, La-ZSM-5 and Ca-La-ZSM-5 were similar to the parent H-ZSM-5 as observed in XRD and FE-SEM analysis. The addition of both Ca and La ions, and their co-impregnation affects the acidity of parent H-ZSM-5 zeolite. In addition, Ca and La ions also induced the formation of basic sites in the zeolite framework. DME conversion of over 97% was observed over all catalyst systems during the 2 h time on stream. Ca-ZSM-5 showed the highest selectivity to light olefins especially propylene due to the presence of weak and medium acid sites.